The Design of A Telegram IoT-based Chicken Coop Monitoring and Controlling System - Prasetyo Adinegoro; Muhammad Hisyam Habbani; Robiatul Akhlakul Karimah; Yoyok Adisetio Laksono (JPSE (Journal of Physical Science and Engineering), 2020)
Less ideal chicken coop condition is one reason for the low productivity of chickens in Indonesia. Based on this condition, breeders need monitoring and control devices that can be used easily anywhere and anytime. In this study, the monitoring and control devices based on the Internet of Things (IoT) were successfully designed using the ESP8266 microcontroller. The monitoring system used a DHT11 temperature sensor while the controller used a bulb and fan as the actuator. Monitoring data and control commands were displayed via Telegram. Coop testing was carried out with three different treatments-the light was on, the fan was on, and both were on-resulting in temperature and humidity measurement data ranging from 24–32 ºC and 61–78%, respectively. Therefore, this monitoring and control device can prevent the conditions of the chicken coop that are ideal less so that chickens' productivity increases.DOI: http://dx.doi.org/10.17977/um024v5i22020p056